Modern recording techniques : a practical guide to modern music production - Huber, David Miles; Caballero, Emiliano; Runstein, Robert E. (New York, NY : Routledge, 2024)
"Modern Recording Techniques is the bestselling, authoritative guide to sound and music recording. Whether you're just starting out or are looking to improve your skills, this book provides an in-depth guide to the art and technologies of music production and is a must-have reference for all audio bookshelves. Using its familiar and accessible writing style, this new edition has been fully updated, presenting the latest production technologies and including detailed coverage of DAWs, networked audio, MIDI, signal processing and much more. Modern Recording Techniques is supported by a host of video tutorials which provide additional listening and visual examples, making this text essential reading for students, instructors and professionals. This updated tenth edition includes: newly expanded "Art and Technology" chapters, providing more tips, tricks and insights for getting the best out of your recording, mixing, monitoring and mastering; an expanded MIDI chapter to include MIDI 2.0; more in-depth coverage of Digital audio and the Digital Audio Workstation; greater coverage of immersive audio, including Dolby Atmos Production"--Provided by publisher.
Includes index.
Keywords: Sound -- Recording and reproducing; Magnetic recorders and recording; Digital audiotape recorders and recording